2010
DOI: 10.2308/accr.2010.85.5.1743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Technical Department’s Advice, Quality Assessment Standards, and Client Justifications on Auditors’ Propensity to Accept Client-Preferred Accounting Methods

Abstract: We conduct an experiment to investigate whether the effects of an SAS No. 90-like quality assessment standard (QAS) on auditors’ decision to accept a client-preferred accounting method is jointly moderated by the nature of advice from an audit firm’s technical department and the strength of the client’s justification. Results indicate that, in the absence of advice, the presence of QAS does not affect auditors’ decision, regardless of client justification strength. However, in the presence of advice from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Ng and Shankar () also study interactions within the firm and investigate the impact of Quality Assessment Standards (QASs) on auditors' decisions to accept client preferred accounting alternatives and how clients' justification and nature of technical departments' recommendations jointly influence these decisions. Results indicate that, without advice from the technical department, auditors' decisions to accept the client‐preferred method are significantly influenced by the strength of the client's justification, but not by the presence of a QAS.…”
Section: Literature Review By Audit Taskmentioning
confidence: 99%
“…Ng and Shankar () also study interactions within the firm and investigate the impact of Quality Assessment Standards (QASs) on auditors' decisions to accept client preferred accounting alternatives and how clients' justification and nature of technical departments' recommendations jointly influence these decisions. Results indicate that, without advice from the technical department, auditors' decisions to accept the client‐preferred method are significantly influenced by the strength of the client's justification, but not by the presence of a QAS.…”
Section: Literature Review By Audit Taskmentioning
confidence: 99%
“…However, the authors posit that this can only occur to the extent that the client"s preferred treatment can be reasonably justified as a sufficiently acceptable method. Ng and Shankar (2010) investigate how advice from an audit firm"s technical department and the strength of the client"s justification for their preferred treatment moderate the findings of Kadous et al (2003) by changing auditors" reasonableness constraints. The results suggest that quality assessments do reduce auditors" agreement with their client"s preferred treatment when the audit firm"s technical department explicitly advises the use of the most appropriate method (which differs from the client"s preference) and when the client"s justification for their preferred treatment is strong.…”
Section: Motivated Reasoning Within Reasonableness Constraintsmentioning
confidence: 99%
“…Thus, persuasive opportunistic disclosures can shift the reasonableness constraint on short investors" natural goals to assess the likelihood of loss as high as possible. Factors that shift reasonableness constraints against individuals" preferences tend to counteract the effects of directional goals to reach a preferred conclusion (e.g., Peecher et al 2010, Ng andShankar 2010). The extent to which prospective investors" judgments can similarly decrease in response to management"s opportunism depends upon how strongly the assimilation effect predicted in H1 already decreased their judgments (i.e., how close they already are to the lowest reasonable judgment in the objective amendment condition due to a heuristic incorporation of additional low probability lawsuits).…”
Section: Emphasis Framing Theorymentioning
confidence: 99%
“…Thus, depending on when the staffing decision is made, auditors may or may not be a priori aware that an expert will be consulted on a specific issue. Although recent accounting research has shown that both formal and informal advice can impact audit judgment (e.g., Ng and Shankar ; Shankar and Ng ; Kadous et al ), this research has not examined whether auditors' awareness that experts will be consulted influences their advice‐taking behavior. Nevertheless, research in psychology indicates that task factors can impact the level of effort that advisees put into a task, causing more or less overreliance on advice (Gino et al ).…”
Section: Introductionmentioning
confidence: 99%